Músicos e relações de trabalho no município de Toledo/PR - Nardi , Guilherme Cezar (2021)
The following research deals with critically analyzing, through historiographical theories and methods, the life of musician workers in the city of Toledo - PR from the 1960s to 2020. This study starts from the point of history seen from below, with this, we can seeking an understanding of the reality of underprivileged classes giving voice to new historical subjects, I believe that this factor democratizes subjects within history. As a methodological process, I used interviews with local musicians based on their experience as workers. It is concluded that the notions built on the musician's identity have a conception that distances these subjects from the understanding of their place in the music production chain.